Polar Science and Global Climate: An International Resource for Education and Outreach - Kaiser, Bettina; Allen, Becky; Zicus, Sandra (Pearson Education Limited, 2010)
The Polar Resource Book (PRB)-Polar Science and Global Climate: AnInternational Resource for Education and Outreachwas created in 2010 to ensure efforts catalyzed by the International Polar Year (IPY) 2007-2008 will continue to inspire educators, students, and emerging polar researches into the next generation with a shared commitment to outreach and education. It comprises information on polar research and the history of the IPY. It addresses climate change related issues from the perspectives of the Indigenous population in the Arctic. It provides a selection of teaching resources on six polar themes (atmosphere, ice, ocean, land, people and space) and showcases large-and small-scale education and outreach projects successfully carried out during the IPY. At the time, the project received support from a wide range of actors who are a part of the IPY community, the World Meteorological Organization (WMO), the International Science Council (ISC), as well as the Canadian IPY Secretariat and IPY program, the National Academies of the United States, the United Nations Environmental Program (UNEP) and the organising committee of the flagship IPY Oslo Science Conference (OSC), and the Association of Polar Early Career Scientists (APECS).